ANALISIS PENERAPAN KURIKULUM MERDEKA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SDN 03 RANAH BATAHAN - Rali Tasman; Jonaidi Jonaidi; Masri Masri; Ismail Syakban (Jurnal Manajemen Pendidikan, 2025)
Objective: This study aims to analyze the implementation of the Independent Curriculum in Islamic Religious Education (PAI) at SD 03 Ranah Batahan focusing on lesson planning, learning implementation, and assessment practices. Methods: The research used a qualitative descriptive approach with data collected through interviews, observations, and documentation involving PAI teachers, school principals, and students. Data were analyzed using Miles and Huberman’s model, including data reduction, data display, and conclusion drawing. Results: The findings reveal that planning documents such as ATP and Modul Ajar have been prepared, but their implementation varies according to teachers’ understanding. Learning activities generally follow the principles of differentiated learning; however, teachers still face challenges in applying diagnostic assessments consistently. Novelty: The novelty of this study lies in its focus on elementary-level PAI learning practices within rural school contexts, showing unique challenges and strategies in adapting the Independent Curriculum